The Relationship between Emotional Maturity and Physical Education Learning Outcomes in MA Al Urwatul Wutsqo Students - Syafa'at, Muchammad Arju; Zoki, Achmed; Setyawan, Risfandi; Hamid, Faisol (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
This study aimed to investigate the relationship between emotional maturity and learning outcomes in Physical Education among students of MA Al Urwatul Wutsqo. Specifically, the study sought to determine whether emotional maturity significantly correlates with academic achievement in Physical Education. A quantitative correlational design was employed. The population comprised all students of MA Al Urwatul Wutsqo, with 60 participants selected through simple random sampling. Data were collected using an emotional maturity scale based on indicators and a Physical Education learning outcome test, both of which had been previously validated for reliability. Data analysis included descriptive statistics and Pearson Product Moment correlation at a significance level of α = 0.05 using SPSS version 20.0. The results revealed a correlation coefficient of r = 0.093 with a significance value of 0.482 (p > 0.05), indicating no significant relationship between the two variables. These findings suggest that psychomotor factors, learning motivation, teaching quality, and direct motor experience are more dominant determinants of learning outcomes in Physical Education than emotional maturity alone.